Carrot or stick: CSR disclosures by Southeast Asian companies. Issue 4 (30th July 2018) - Arena, Claudia; Liong, Ronald; Vourvachis, Petros
Abstract : Purpose: Motivated by legitimacy theory, this paper aims to examine comprehensively corporate social responsibility (CSR) disclosure in Southeast Asian (Association of Southeast Asian Nations [ASEAN]) countries with the aim of disentangling whether such disclosures are the result of a proactive stance or a reaction to regulations. Design/methodology/approach: After a content analysis of CSR stand-alone reports that relies on the Global Reporting Initiative as the basis for comparison, a multivariate analysis is carried out while controlling for firm-specific incentives and industry, country and year fixed effects. Findings: The paper finds that CSR disclosure increased across the entire ASEAN. Although this increase cannot be directly ascribed to the introduction of regulations in Indonesia and Malaysia, the latter may have impacted choices of disclosure media. In countries where reporting requirements have become mandated, mandatory reporters show low levels, and voluntary reporters high levels, of CSR disclosure. The paper also finds that the attainment of CSR awards is related to disclosure. Additional analyses reveal a substitution effect between voluntary and mandatory incentives in countries with high levels of law enforcement. Practical implications: The evidence suggests that the introduction of regulations can be effective in improving the level and breadth of CSR reporting only in the presence of institutions that ensure the enforcement of the disclosure regulations. Social implications: The evidence suggests that organizations are reluctant to report on issues such as child labor, human rights and corruption. Organizations opportunistically employ related disclosure strategies that deviate from the underlying CSR performance. Originality/value: The paper analyzes not only the level and breadth of CSR disclosure but also the motivation for its use across the still under-investigated ASEAN area, thus allowing an examination of the influence of institutional incentives above and beyond the firm-specific factors that drive CSR activities.